Unusual case of a myxoma atrial left presenting with recurrent monoparesis - Baztarrica, Gabriel E. Pérez; Baros, Andres Wong; Chiriboga, Nadia; Gil, Andres Felipe; Negrete, Jenny Ramos; Cevallos, Xavier Centeno; Maldonado de la Torre, Marco José; Erique, Michaelly; Aviles, Ines Hernàndez; Solorzano, Reneiro Velez; Moran, Ariot Vinicio Sancan; Goncalves, Fabio Oscar Domborovski; et al. (SA Heart Journal, 2019)
Usually, embolism is described from cardiac or large artery disease. Atrial fibrillation is the most common cause of cardiogenic emboli in stroke. Myxoma is responsible in only a few cases. We describe here a case of a patient who presented with recurrent pure left brachial monoparesis as a manifestation of a cardiac myxoma.